Foreign Guests at the Institute of International Relations in the 2nd half of 1990 (Czech Journal of International Relations, 1992)
The Institute of International Relations established close relations with the Austrian Institute for International Policy. Its director Prof. H. Neuholdl, who was in Prague on 9.-10.7. 1990, expressed interest in mutual cooperation in the form of a joint research project on Czechoslovak-Austrian relations and participated in a round table discussion on issues of cooperation between the two countries, on the German issue, Austrian foreign policy and European integration.On July 16, 1990, a meeting of researchers from the úMV and other Czechoslovak institutions took place. institution with a delegation of the American Chicago Council on Foreign Relations, led by the president of this institution, J. E. Rielly. After the introductory interpretation of MS. experts, which related to economic reform, the upcoming reprivatization and reconstruction of the Czech Republic. financial and price systems, followed by a discussion. On days 25.-27.7. 1990 the representative of the Association of the European Monetary Union H. Colligton was a guest of the úMV. He participated in a round table discussion on monetary issues.Prominent Soviet political scientist, director of the Institute of the USA and Canada AV USSR academician G. A. Arbatov stayed in Prague on 28.-30.7. 1990. During his visit, he was received by President V. Havel, Deputy Prime Minister and Minister of Foreign Affairs J. Dienstbier, Minister of Finance V. Klaus and Chairman of the Foreign Committee of the SL FS of Czechoslovakia Prof. V. Komárke. He then met in Bratislava with the chairman of the CSFR FS A. Dubček and other prominent Slovak political representatives and scientists. The discussion at the round table in the úMV focused on domestic political developments and foreign policy of the USSR, European integration and USSR-USA relations.